Spatial Monitoring of Wind Erosion and Some Heavy Metals in Suspended Load of Tabas City - H. Emami; M. Memarzadeh (مجله آب و خاک, 2023)
Introduction Wind Erosion is the natural process of transportation and deposition of soil by wind. It is a common phenomenon occurred mostly in dry, sandy soils or anywhere the soil is loose, dry, and finely granulated. Heavy metals are found in the environment and soils may become contaminated by accumulation of heavy metals through emissions from the rapidly expanding industrial areas, mine tailings, disposal of high metal wastes, leaded gasoline and paints, land application of fertilizers, animal manures, sewage sludge, pesticides, wastewater irrigation, coal combustion residues, spillage of petrochemicals, and atmospheric deposition. Soils are the major sink for heavy metals released into the environment by the aforementioned anthropogenic activities and their total concentration in soils persists for a long time after their introduction. The heavy metal contamination of soil and its potential risks to humans and the ecosystem is a significant concern. Windy deposition, which is the process of heavy metals being transported by erosive winds and deposited onto soil, is one of the sources of heavy metal contamination. Due to the geographical situation and climatic conditions such as arid soil, erosive winds are blown in periods of year in Tabas. Since wind are erosion is severe in this area, huge amounts of wind deposition accompanied with erosive winds entered into this town. Heavy metals through the windy deposition are suspended, translated and finally deposited in residential regions, which can create some problems for human health. Therefore, the knowledge of wind erosion and the human risk of these deposits is essential. The aim of this research was to determine the rate of wind erosion and the concentration of some heavy metals in these deposits. Materials and Methods For this purpose, the rate of suspended load was measured monthly from February 2021 to January 2022. Based on previous information from the erosive winds and storms, suspended depositions were gathered in some directions (north, northwest, northeast, west and southwest) of the Tabas entrance. In addition, the suspended load in the city center of Tabas was also measured. The cumulative load of suspended depositions was measured monthly and the concentration of some heavy metals such as manganese (Mn), iron (Fe), cupper (Cu), and zinc (Zn) were measured in these suspended particles.  Soil digestion was made by Aqua regia (nitric acid and chloridric acid; ratio of 3:1), and after then atomic absorption was used to measure the total concentration of above heavy metals. Results and Discussion The results indicate that Tabas experiences significant wind deposition of suspended loads, with the highest rates entering from the northeast direction and the lowest rates from the southwest direction. This pattern aligns with the wind rose of Tabas, which illustrates the prevailing wind directions in the region. Additionally, substantial suspended loads are observed in the northwest and north directions. The variations in suspended load discharge reveal that the maximum discharge occurs in the city center of Tabas during the months of June and July 2021. This corresponds to the arid climate conditions of these months, where plant growth is limited, soil cohesion is low, and loose soil particles on the surface are susceptible to wind forces. As a result, these loose particles are easily detached by the wind, contributing to the high levels of suspended load. Regarding the spatial variation of heavy metals in suspended particles, the cumulative concentrations of Mn, Fe, Cu, and Zn are found to be higher in the west, northwest, north, and west directions, respectively. This suggests that these heavy metals are transported and deposited in specific areas within Tabas due to the prevailing wind patterns. In terms of temporal variation, the highest concentrations of Mn and Fe in suspended particles are observed in April 2021, predominantly in the northeast and west directions, respectively. On the other hand, the highest concentrations of Cu and Zn are found in May 2021, with the southwest and northeast directions being the primary deposition areas for each metal, respectively. These findings highlight the spatial and temporal dynamics of suspended load and heavy metal deposition in Tabas, emphasizing the influence of wind patterns and climatic conditions on these processes. Understanding these variations is crucial for assessing the potential risks associated with heavy metal contamination and implementing appropriate mitigation measures in the region. Conclusion The results of this research showed that most contents of the suspended load are entered from the northeast direction into Tabas. In addition, the spatial variation of heavy metals indicated that the concentrations of studied heavy metals (Mn, Fe, Cu, and Zn) in suspended particles, especially in the western, northwestern, and northern in spring, are very high and they can cause carcinogenic effects on human life. Therefore, the management practices should be mostly made in these directions to control or reduce soil erosion and reduce its damage effects.